A Contribution to the knowledge of the uraniferous lutites of the province of San Juan (Argentina) - Angelelli, Victorio; Ortega Furlotti, Armando (Organismo Internacional de Energía Atómica, 1958)
Fil: Angelelli, Victorio Comisión Nacional de Energía Atómica; Argentina